2015
DOI: 10.3109/14756366.2015.1063621
|View full text |Cite
|
Sign up to set email alerts
|

Phenols displaying tyrosinase inhibition from Humulus lupulus

Abstract: Tyrosinase is the rate-limiting enzyme for the production of melanin and other pigments via the oxidation of L-tyrosine. The methanol extract from Humulus lupulus showed potent inhibition against mushroom tyrosinase. The bioactivity-guided fractionation of this methanol extract resulted in the isolation of seven flavonoids (1-7), identified as xanthohumol (1), 4 0 -Omethylxanthohumol (2), xanthohumol C (3), flavokawain C (4), xanthoumol B (5), 6-prenylnaringenin (6) and isoxanthohumol (7). All isolated flavono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
1
9
0
1
Order By: Relevance
“…IC 50 values in the range 28-42 µM have been reported for two lignans isolated from Opilia amentacea leaves [112] (Figure 13), whereas particularly effective against the monophenolase activity of the enzyme were flavonolignans from the seeds of Silybum marianum (IC 50 in the range 1.7-4.9 µM) ( Figure 13) [113] as well as, although with a lower strength, hydroxylated phenones from Syzygium polyanthum leaves [114] (Figure 14). Higher inhibition against monophenolase than diphenolase activity of mushroom tyrosinase were reported also for xanthohumol and other chalcones isolated from Humulus lupulus [115] ( Figure 14). Higher inhibition against monophenolase than diphenolase activity of mushroom tyrosinase were reported also for xanthohumol and other chalcones isolated from Humulus lupulus [115] ( Figure 14).…”
Section: Natural Phenolic Inhibitors Of Mushroom Tyrosinasementioning
confidence: 74%
See 2 more Smart Citations
“…IC 50 values in the range 28-42 µM have been reported for two lignans isolated from Opilia amentacea leaves [112] (Figure 13), whereas particularly effective against the monophenolase activity of the enzyme were flavonolignans from the seeds of Silybum marianum (IC 50 in the range 1.7-4.9 µM) ( Figure 13) [113] as well as, although with a lower strength, hydroxylated phenones from Syzygium polyanthum leaves [114] (Figure 14). Higher inhibition against monophenolase than diphenolase activity of mushroom tyrosinase were reported also for xanthohumol and other chalcones isolated from Humulus lupulus [115] ( Figure 14). Higher inhibition against monophenolase than diphenolase activity of mushroom tyrosinase were reported also for xanthohumol and other chalcones isolated from Humulus lupulus [115] ( Figure 14).…”
Section: Natural Phenolic Inhibitors Of Mushroom Tyrosinasementioning
confidence: 74%
“…Higher inhibition against monophenolase than diphenolase activity of mushroom tyrosinase were reported also for xanthohumol and other chalcones isolated from Humulus lupulus [115] ( Figure 14). Higher inhibition against monophenolase than diphenolase activity of mushroom tyrosinase were reported also for xanthohumol and other chalcones isolated from Humulus lupulus [115] ( Figure 14). Higher inhibition against monophenolase than diphenolase activity of mushroom tyrosinase were reported also for xanthohumol and other chalcones isolated from Humulus lupulus [115] (Figure 14).…”
Section: Natural Phenolic Inhibitors Of Mushroom Tyrosinasementioning
confidence: 74%
See 1 more Smart Citation
“…XH has previously been reported to possess inhibitory effects on melanogenesis in B16F10 mouse melanoma cells [ 26 ] while it inhibits activity of mushroom tyrosinase in a cell-free system [ 25 ]. However, to date, there are no reports on the effects of XH on melanogenesis in human melanocytes; this is a critical issue since most depigmenting candidates in the flavonoid group have shown opposite effects on melanogenesis in mouse and human cells in earlier studies [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that XH inhibited mushroom tyrosinase activity in an acellular system [ 25 ] and inhibited melanin synthesis in B16F10 mouse melanoma cells. The authors concluded that XH is a skin-whitening agent [ 26 ].…”
Section: Introductionmentioning
confidence: 99%